Gerakan Kampus Hijau Melalui Kegiatan Pembersihan Gulma dan Penanaman Tanaman Mint Sebagai Apotek Hidup di Universitas Sunan Giri Surabaya - Dharma Setiawan Negera; Fadhil Muhammad Ramadhani; Didit Darmawan; Rommy Hardyansah; Syafra'Ie Mw (CV Putra Publisher, 2026)
The campus environment plays a strategic role in shaping environmental awareness and pro-environmental behavior among the academic community as part of sustainable development. However, environmental cleanliness management and the optimal use of campus land remain common challenges faced by many higher education institutions. Therefore, collaborative efforts are needed that focus not only on cleanliness but also on the educational and productive use of the environment. This Community Service activity aims to support the realization of a green campus movement through weed removal and the planting of mint plants as part of the utilization of a living pharmacy. The activity was implemented at Universitas Sunan Giri Surabaya as an example of participatory campus environmental management. The method used was Participatory Action Research (PAR), which actively involved students in all stages of the activity, including planning, implementation, and evaluation. The implementation focused on cleaning underutilized campus areas and planting mint plants as an effort to promote greening as well as health education. The results indicate an increase in students’ awareness and participation in maintaining campus environmental cleanliness and sustainability, along with more productive and valuable land use. This activity is expected to strengthen an environmentally oriented and sustainable campus culture.